Analisis Persediaan Bahan Baku terhadap Kontinuitas Pada Industri Kertas Handmade - Edi Arisandi (SMARTINDO, 2023)
Raw materials are a very important part of the smooth running of a production, lack of raw materials can disrupt theproduction process, while excess raw materials can cause storage costs to increase and other costs. This study aims todetermine how to control raw material inventory on the continuity of productionin the handmade paper industry, inaddition to knowing the possibility of increasing the efficiency of raw material inventory using the Economic OrderQuantity (EQQ) model. This research is located in Balangan Regency. The type ofresearch used in this research is descriptive quantitative, which is an analysis of data by describing or describing the data that has been collected asit is withoutthe intention of making conclusions that apply to the public. The types of data used in this study are quantitative data and qualitative data. There are two sources of data used in this study, namely primary data and secondary data. Methods of data collection are done by means of observation and interviews. The results of this study indicate that the efficiency of raw material inventory at the company can be increased by using the Economic Order Quantity (EOQ) model and the useof the company's Economic Order Quantity (EOQ) can increase savings or low costs compared to using the method applied by the company today so that it is good for company sustainability.